Implementation of state space method for forecasting the number of patients with HIV/AIDS infectious diseases - Wiwik Wiyanti (Universitas Negeri Semarang, 2023)
This research concerns about the implementation of the State Space method for forecasting to the number of people with infectious diseases (a case study is the number of people with HIV/AIDS) in the Indonesia. The research was conducted from August 2022 to November 2022. The data obtained from kagle, namely new cases of HIV/AIDS infection. In this research, HIV data from 1990 to 2019 was used for forecast analysis. The forecasting method in this research is State Space method. Predict of new cases will found in 2020, 2021, 2022 and 2023 are 14095,14139, 14167 and 14184 respectively. The forecast analysis result obtained that the mean absolute percentage error is 0,4%.